The Role of Architecture in Early Educational Stages: Firmitas, Utilitas and Venustas - Atrio Cerezo, Santiago; Eslava Cabanellas, Clara (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2018)
The aim of this article is to theoretically support the pedagogical possibilities of architecture in the early stages of education, especially in early Childhood education (3-6 years). It is claimed here the value of architecture as a setting, means and content for education, thus posing a dialogue between architecture and pedagogy. Some key historical moments and authors that have contributed to forge this symbiosis have been identified and outlined. They have also been contrasted the theoretical views of the researcher with the practical experiences of classroom professionals, so that new ways of cooperation between the fields of architecture and school may be established.
Keywords: architecture; childhood; education; constructions; environment; setting